How do organizational practices relate to perceived system safety effectiveness? Perceptions of safety climate and co-worker commitment to safety as workplace safety signals. (September 2019) - Stackhouse, Madelynn; Turner, Nick
Abstract: Introduction : Integrating safety climate research with signaling theory, we propose that individual perceptions of safety climate signal the importance of safety in the organization. Specifically, we expect that three work-related organizational practices (training effectiveness, procedure effectiveness, and work pressure) relate to the broader risk control system in the workplace via individual perceptions of safety climate as a broad management signal. Further, we expect this broad management signal interacts with a local environmental signal (co-worker commitment to safety) to amplify or diminish perceived system safety effectiveness. Method : In a field study of oil and gas workers ( N =  219; Study 1), we used mediation modeling to determine the relationships between work-related organizational practices, perceived safety climate, and perceived safety system effectiveness. In a field study of railway construction workers ( N  = 131; Study 2), we used moderated mediation modeling to explore the conditional role of co-worker commitment to safety. Results : We found that training effectiveness, procedure effectiveness, and work pressure predicted perceived system safety effectiveness indirectly via perceived safety climate (Studies 1 and 2) and that these indirect paths are influenced by co-worker commitment to safety (Study 2). Conclusions : Findings suggest that perceived safety climate is driven in part by work practices, and that perceived safety climate (from managers) and co-worker commitment to safety (from the local environment) interact to shape workplace safety system effectiveness. Practical applications : The insight that training, procedures, and work pressure are meaningful predictors of perceived safety climate as a signal suggests that organizations should be cognizant of the quality of work-related practices for safety. The insight we offer on the competing versus complimentary nature of managerial safety signals (perceived safety climate) and co-worker safety signals (co-worker commitment to safety) could also be used by safety personnel to develop safety interventions directed in both areas. Highlights: Training effectiveness, procedure effectiveness, and work pressure are antecedents to perceived safety climate. Co-worker commitment to safety is a signal that can diminish or enhance the positive signals from perceived safety climate. Managers should be cognisant of competing and complimentary workplace signals for the value of safety in the organization.